AKAD PARON PERTANIAN CABE PERSPEKTIF HUKUM EKONOMI ISLAM - Mun’im, Abdul (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This research aims to describe the implementation of the Muzara'ah agreement in the agricultural sector by farmers in Sumberanyar Village and its impact on improving the welfare of farmers in Sumberanyar Village. The method used in this research is a qualitative method. Researchers collected data using observation, interviews and documentation methods. From the results of his research, it was found that the contract was carried out verbally on the basis of mutual help and trust. The results of this research show that the profit sharing for rice field owners and sharecroppers in Sumberanyar Village, namely Paron profit sharing in Sumberanyar Village, is carried out using a Muzara'ah agreement, where the agreement is made at the beginning, the sharing of the results has been mutually agreed upon, namely every time the harvest and produce chilies in Some sales are then shared between land owners and sharecroppers. With this profit sharing system, farmers and cultivators in Sumberanyar Village both benefit, no one feels disadvantaged. Keywords; Paron contract, Islamic Economic Law